Developing business ethics theory and integrating economic analysis into business ethics teaching – a conceptualization based on externalities and diminishing marginal utility. Issue 1 (2nd January 2018) - Hirschauer, Norbert; Jantsch, Antje; Musshoff, Oliver
Abstract: Contrary to understandings that treat ethical considerations and economic thinking as separate if not antagonistic issues, we advocate a holistic view that links business ethics to consequentialist economic concepts and their concern about how scarce means should be used for the attainment of (given) ends. We believe that business ethics students will profit from a development of business ethics theory that facilitates an outcome-based evaluation of business strategies anchored in the economic concepts of externalities, game theory, equilibria, efficiency, transaction costs, and diminishing marginal utility. We outline how moral judgments about (socially irresponsible) business behaviors, which often lack theoretical grounding and self-critical examination, can be made both more consistent and transparent through a systematic application of these theoretical concepts. We furthermore point out that, in this evaluative exercise, business ethics analysts should make all assumptions explicit to meet their task of facilitating informed public debates and informed moral choices.